Accommodating the visitor: How museums connect with their present-day populations - Linda Pillière (Anglophonia)
This article analyses the different accommodation strategies to be found in museums in the United Kingdom and the United States. The seventies and eighties witnessed a change in museology towards a new awareness of museums’ social role and the need to improve communication strategies for their visitors. This article will examine the different liguistic strategies that are used in museums in written texts such as labels and panels.